Fiscal decentralization: model of its impact on economic development - Кваша, Тетяна Костянтинівна (Technology audit and production reserves, 2015)
Today, fiscal decentralization is the most important characteristic of modern systematic intergovernmental relations. However, the problem of assessing its impact on economic growth underrepresented in contemporary Ukrainian researches. For Ukraine it is extremely important given the objectives of the Strategy for Sustainable Development «Ukraine-2020» and the program of the government to build an effective system of territorial organization of power in Ukraine with a maximum transfer of functions to the local level, including additional budgetary authority. Existing models of the impact of fiscal decentralization on economic development are analyzed and systematized, possibility of further use of some of them to Ukraine is defined and approach to building an appropriate model for our country using the production function Cobb-Douglas based on regression analysis is proposed.